Effect of lysine succinylation on the regulation of 2-oxoglutarate dehydrogenase inhibitor, OdhI, involved in glutamate production in Corynebacterium glutamicum. Issue 11 (2nd November 2017) - Komine-Abe, Ayano; Nagano-Shoji, Megumi; Kubo, Shosei; Kawasaki, Hisashi; Yoshida, Minoru; Nishiyama, Makoto; Kosono, Saori
Abstract: In Corynebacterium glutamicum, the activity of the 2-oxoglutarate dehydrogenase (ODH) complex is negatively regulated by the unphosphorylated form of OdhI protein, which is critical for L-glutamate overproduction. We examined the potential impact of protein acylation at lysine (K)-132 of OdhI in C . glutamicum ATCC13032. The K132E succinylation-mimic mutation reduced the ability of OdhI to bind OdhA, the catalytic subunit of the ODH complex, which reduced the inhibition of ODH activity. In vitro succinylation of OdhI protein also reduced the ability to inhibit ODH, and the K132R mutation blocked the effect. These results suggest that succinylation at K132 may attenuate the OdhI function. Consistent with these results, the C . glutamicum mutant strain with OdhI-K132E showed decreased L-glutamate production. Our results indicated that not only phosphorylation but also succinylation of OdhI protein may regulate L-glutamate production in C . glutamicum . Abstract : : Succinylation at K132 of OdhI attenuates the OdhI function to inhibit ODH activity and affects L-glutamate production in Corynebacterium glutamicum .